The Effect of Bone Marrow Mesenchymal Stem Cells on Sensory-Motor Function and GAP-43 Protein Expression in Spinal Cord Injury Induced by Weight-Dropping in Rats - Mohsen Rezaei; Mohammad Taghi Mohammadi; Hassan Qoshooni; Farideh Bahrami; Zahra Bahari; Shima Shahyad; Raheleh Halabian (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Spinal cord injuries are usually severe and currently lack effective treatment. Bone marrow stem cells (BMSCs) have significant potential for repair by reducing inflammation, regulating immunity, stimulating angiogenesis, promoting growth, and enhancing cell differentiation. They are promising for treating these injuries by supporting nerve axon growth and myelin regeneration. This study examines the role of BMSCs in addressing the challenges of spinal cord tissue repair. Materials and methods: BMSCs were isolated from the femurs of 150–200 g rats, and after culturing, the third passage was used. Thirty Wistar rats (200–300 g) were divided into three groups: control, lesion control, and BMSC-treated. Spinal cord injury was induced by dropping a 10 g weight on the T13–L1 region. On the eighth day after injury, either a vehicle solution or 1 million BMSCs in 10 μL were injected into the injury site. Evaluations, including the BBB test, hot water withdrawal latency, nerve conduction velocity, LFB staining, and GAP-43 protein expression, were performed using the western blot method. Results: Treatment with BMSCs significantly increased the BBB score, improving hind limb movement in rats. These cells also reduced the reaction time for paw withdrawal and enhanced sensory system function. Furthermore, BMSCs significantly reduced spinal reflex latency and accelerated the compound action potential (CAP) recorded in the gastrocnemius muscle. Moreover, they promoted axon growth and proliferation by increasing GAP-43 protein expression and contributed to improved myelination. Conclusion: The results indicate that the use of BMSCs as a therapeutic approach reduces axon and myelin degeneration while promoting neuronal growth and repair. These reparative effects at the molecular level were associated with increased GAP-43 protein expression and improved sensory and motor function in the hind limbs of animals.